Comparison of Five Protocols of Estrous Synchronization on Reproductive Performance of Hu Sheep - Yu, Xiaojie; Bai, Yuanyuan; Yang, Jiangfeng; Zhao, Xiaokun; Zhang, Lei; Wang, Jing (Frontiers in Veterinary Science, 2022)
The purpose of this study is to compare five protocols of estrous synchronization for Hu ewes to obtain the most effective and economical protocol, to apply the advantageous scheme in large-scale sheep farming. Multiparous Hu ewes (n = 150) were randomly divided into five groups, and all ewes were administered FGA vaginal sponge. The sponges of the first three groups (Group Ⅰ, Ⅱ, Ⅲ) were removed on the 11th day and PGF2α was injected intramuscularly on the 9th day. Group Ⅰ received GnRH at 36th hour after withdrawal. Group Ⅱ was injected 330 IU of PMSG on the 9th day. The combination of GnRH and PMSG was treated in Group Ⅲ at the same time as Group Ⅰ and Group Ⅱ. The sponges of the latter two groups (Group Ⅳ and Ⅴ) were removed and PMSG was injected on the 13th day. PGF2α was administered on the 12th day in Group Ⅳ. The results showed that: (1) on the whole, the average percentage of estrous ewes in the period of 24 - 36 h and 36 - 48 h after removal were significantly higher than other three periods, and that of the period of 60 - 72 h was significantly lower than the first three periods after removal; (2) there was no significant difference in percentages of estrous ewes in any of the five time periods, sponge loss rate, vaginitis rate, total percentage of estrous ewes, conception rate, single lambing rate, twinning rate and multiple lambing rate of ewes among five protocols; (3) total percentage of estrous ewes and conception rate were more than or equal to 80% in the Group Ⅱ and Group Ⅲ, and the twinning lamb rate of the Group Ⅱ protocol was 70%; (4) there was no difference in lambing rate of ewes among Group Ⅱ, Ⅲ, Ⅳ and Ⅴ; (5) the Group Ⅲ had the highest drug cost of CNY 22.5. In conclusion, considering the lambing rate, twinning lamb rate, and drug cost, Group Ⅱ was the most advisable for application and promotion in large-scale sheep farms among these five protocols of estrus synchronization.